Cross-Border Banking in Europe: Implications for Financial Stability and Macroeconomic Policies - LANE, PHILIP RICHARD (Centre for Economic Policy Research, 2011)
Understanding the role of banks in cross-border finance has become an urgent priority. Cross-border banks have played a central role in the dynamics of the global crisis of 2007-2009. First, European banks had a surprisingly large exposure to the US securitised asset markets, which arose to a significant extent through global banks acting either on the buying or selling side in these markets. Second, the breakdown in credit and asset markets was an international phenomenon, with cross-border linkages suffering disproportionately due to greater information problems vis-a-vis cross-border counterparties and the differences in regulatory regimes. Third, currency mismatches in funding became evident, with European banks suffering a dollar shortage that ultimately required resolution through a major currency swap initiative among the main central banks. Fourth, the provision of fiscal support for distressed banks was especially problematic in relation to cross-border activities. The rescue of multi-country banks, such as Dexia and Fortis, required the governments involved to devise ad hoc, ex-post burden-sharing agreements. In relation to emerging Europe, there were also fears that the policies of home-country governments might encourage parent banks to fail to support the operations of affiliates. This report analyses key aspects of cross-border banking, takes a European focus and derives policy recommendations based on them.
PUBLISHED
London, UK
Keywords: Economics; Banking